2015
DOI: 10.1007/s11695-015-1882-5
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Bypass-Related Effects on Glucose Control, β Cell Function and Morphology in the Obese Zucker Rat

Abstract: Combined molecular, cellular and histological analyses of pancreatic function suggest that weight loss alone, and not the enhancement of GLP-1 responses, is predominant for the short-term β cell protective effects of RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 37 publications
9
27
2
Order By: Relevance
“…In accordance with previous human (Kenler et al, 1990; Olbers et al, 2006; Thomas and Marcus, 2008) and rodent (Zheng et al, 2009; le Roux et al, 2011; Shin et al, 2011b; Hao et al, 2016) studies, we demonstrated that RYGB reduces HF intake and preference using an established rat model (Hankir et al, 2015; Seyfried et al, 2016). We found that this was associated with widespread reductions in brain MOR availability, particularly in the striatum.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with previous human (Kenler et al, 1990; Olbers et al, 2006; Thomas and Marcus, 2008) and rodent (Zheng et al, 2009; le Roux et al, 2011; Shin et al, 2011b; Hao et al, 2016) studies, we demonstrated that RYGB reduces HF intake and preference using an established rat model (Hankir et al, 2015; Seyfried et al, 2016). We found that this was associated with widespread reductions in brain MOR availability, particularly in the striatum.…”
Section: Discussionsupporting
confidence: 91%
“…All abdominal surgical procedures were performed after an overnight fast by a bariatric surgeon according to a previously established protocol (Hankir et al, 2015; Seyfried et al, 2016). Briefly, animals were anesthetized with 5% isoflurane in 2 l/min oxygen and then maintained on 1.8–2.3% isoflurane in 0.5 l/min oxygen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research on the mechanism by which RYGB relieves diabetes‐associated obesity is important . The ZDF rat, a genetically engineered rat model of obesity associated with insulin resistance, dyslipidemia, and other complications, has been chosen to assess the effect of RYGB in many previous studies . In the present study, RYGB surgery obviously decreased endotoxemia‐associated indices, plasma LPS concentrations, and serum and adipose tissue concentrations of the inflammatory cytokines TNF‐α and IL‐1β.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, we performed RYGB in Zucker diabetic fatty (ZDF) rats, a diabetic rat model of insulin resistance, dyslipidemia, and other complications. Many early and recent studies have used this experimental model to assess the effects of RYGB on glucose homeostasis . providing a quite precise approximation of obesity associated with T2D in humans.…”
Section: Introductionmentioning
confidence: 99%